Freehand Elastography for Determination of Breast Cancer Size: Comparison With B‐Mode Sonography and Histopathologic Measurement. (1st August 2014) - Zippel, Douglas; Shalmon, Anat; Rundstein, Arie; Novikov, Ilya; Yosepovich, Ady; Zbar, Andrew; Goitein, David; Sklair‐Levy, Miri
Abstract : Objectives: Elastography assesses the strain of soft tissues and is used to enhance diagnostic accuracy in evaluating breast tumors, but minimal data exist on its ability to accurately assess tumor size. This study was performed to assess the preoperative accuracy of measuring the size of biopsyproven breast cancer lesions with elastography and conventional B‐mode sonography compared with the reference standard size measured by histopathologic examination. Methods: Elastography and conventional B‐mode sonography were performed on 69 women with histologically proven breast cancer, and tumor sizes on both modalities were recorded. These measurements were compared with the final pathologic size, which was used as the reference standard. The sizes and differences between sonographic, elastographic, and pathologic measurements were statistically tested, and an analysis of equivalence to the reference standard was performed using Bland‐Altman plots. Results: There was a significant difference between sizes on elastography and pathologic examination, with elastography overestimating the tumor size ( P = .0187). Sonography slightly underestimated the tumor size, but this finding was not significant ( P = .36). Bland‐Altman plots confirmed that sonography but not elastography was an acceptable standard compared with the pathologic size. Conclusions: Breast elastography but not B‐mode sonography overestimates the size of breast tumors compared with the final pathologic size.